(1)2x-y=3 5x+2y=-6 (2)2/3x-1/2y=-1 1/2x+1/5y=5
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 21:07:10
(1)2x-y=35x+2y=-6(2)2/3x-1/2y=-11/2x+1/5y=5(1)2x-y=35x+2y=-6(2)2/3x-1/2y=-11/2x+1/5y=5(1)2x-y=35x+2y
(1)2x-y=3 5x+2y=-6 (2)2/3x-1/2y=-1 1/2x+1/5y=5
(1)2x-y=3 5x+2y=-6 (2)2/3x-1/2y=-1 1/2x+1/5y=5
(1)2x-y=3 5x+2y=-6 (2)2/3x-1/2y=-1 1/2x+1/5y=5
前一个
(1)*2+(2)得到X=0,Y=-3
后一个
(2)*4-(1)*2得到y=10x=6
(1)2x-y=3 ①
5x+2y=-6②
①×2 4x-2y=6 ③
②+③ 9x=0 ∴x=0 ④
④代入① 解得y=-3
(2)2/3x-1/2y=-1①
1/2x+1/5y=5②
①×3/4 1/2x-3/8y=-3/4③
②-③23/40y=23/4 ∴y=10④
④代入② 解得x=6
x+y/2+x-y/6=5 2(x+y)-3(x-y)=-2
6(x-y)-2(x+y)=14 3(x-y)+(x+y)=5
{6(x-y)-7(x+y)=21 {2(x-y)-5(x+y)=-1
2(x+y)-3(x-y)=1 6(x+y)+(x-y)=51
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
(x-y)/(x+y)=3求( 3x-2y-1)/(x+y-5)
{(x+y)/2+(x-y)/3=1,(x+y)-5(x-y)=2.求x=?,y=?
{x+y=1 ,xy=-6{x(2x-3)=0,y=x²-1{(3x+4y-3)(3x+4y+3)=0,3x+2y=5{(x-y+2)(x+y)=0,x²+y²=8{(x+y)((x+y-1)=0,(x-y)(x-y-1)=0
已知x-y/x+y=3,求代数式5(x-y)/x+y-x+y/2(x-y)
已知:2x+y=6,x-3y=1 求7y(x-3y)(x-3y)-2(3y-x)(3y-x)
化简[(3x+4y)^2-(2x+y)(2x-y)+(-x+y)(5x-y)]除以-2y,其中x=-1,y=1
x+y/2+x-y/3=5/6;x=y/6-x-y/3=1/2
初二上学期方程题 4x+y=5 5x+4y=63x-2y=1 2x+3y=13x-2y=7 7x+5y=32x+3y=17 2x-y=-4x+5y=6 2x+y=23x-6y=4 3x+2y=52x+y=73x-4y=53x+y=1x-2y=-1x+y=42x+3y=92x-3y=74x+5y=3x+y=20004x+6y=90003x+5y=113x-2y=42x+3y=215x-2y=5x+y=54x+3y=182x+3y=16x+4y=132x+3y=40x
3x+2y/4=2x+y/5=x-y+1/6
1、(-y^3)^5/y^3/ y^2+2(-y)^102、(x-y)^7/(y-x)^6+(x+y)^3/(x+y)^23、已知X^a=5,x^b=3,求X^(3a-2b)的值
【2(x-y)^3-8(x-y)^2(x+y)+6y(x-y)^2】/2(x-y)^2=
(x+y)(x-y)+(x-y)^2-(6x^2×y÷2y-2xy^2÷2y)其中x=-3,y=1/3
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2